BLOOD PRESSURE PROFILE IN UNIVERSITY STUDENTS WHO PRACTICE SPORTS VERSUS SEDENTARY INDIVIDUALS - Conceição, Beatriz Rato; Rodrigues, António Filipe Pinto; Coelho, Patrícia Margarida dos Santos Carvalheiro (Seven Editora, 2026)
Hypertension is a clinical condition that has been increasing significantly in recent years, both in the elderly population and in young adults. It is characterized by a persistent elevation of blood pressure and is considered hypertension when systolic blood pressure values ​​are equal to or greater than 140 mmHg and/or diastolic blood pressure values ​​are equal to or greater than 90 mmHg. Hypertension is one of the main risk factors for the development of cardiovascular diseases, and is therefore of great importance.